The Effects of Coffee and Energy Drink on Color Stability of Hybrid Ceramics - Hande Yıldız Dilli; Işıl Sarıkaya (Ankara University, 2021)
Purpose: The aim of this study was to compare the color stability of two different hybrid ceramic materials.Materials amp; Methods: Using the precision cutting device (Micracut, Metcon, Turkey), 36 specimens (12 x 15 x 1 mm) were obtained from Vita Enamic (Vita Zahnfabrik, Germany) and Lava Ultimate (3M ESPE, St.Paul, USA) CAD / CAM blocks. After finishing procedures were completed, all specimens were stored in distilled water for 24 h. Then, the specimens were dried and the initial color measurements were made. L, a, b values were determined using a spectrophotometer (Vita Easy Shade, Vita Zahnfabrik, Germany). The specimens were then divided into 3 test groups and stored in coffee (Nescafe Classic, Turkey) (G2, G5), energy drink (Red Bull, Austria) (G3, G6), and in the distilled water as the control group (G1, G4), for 48 h. After 48 h, the specimens were washed with distilled water and dried. Second color measurements were made. ∆E00 values were calculated using the CIEDE 2000 color-difference formula.Results: Data were analyzed by two-way ANOVA. Multiple comparisons were made with Bonferroni's test. There was a statistically significant difference between 2 ceramics (p=0.035). Generally, Lava Ultimate showed more color change than Vita Enamic. Among the beverages, coffee was significantly different for both ceramics than control and energy drink (p lt;0.05).Conclusion: Lava Ultimate, showed more color change than Vita Enamic. Coffee has also been determined as the most colorant drink for both hybrid ceramics.